Evaluation of Tumor Budding in Primary Colorectal Cancer and Corresponding Liver Metastases Based on H&E and Pancytokeratin Staining - Blank, Annika; Schenker, Carla; Dawson, Heather; Beldi, Guido; Zlobec, Inti; Lugli, Alessandro (Frontiers in Medicine, 2019)
In colorectal cancer, tumor budding is associated with tumor progression and represents an additional prognostic factor in the TNM classification. Tumor buds can be found at the invasive front (peritumoral budding; PTB) and in the tumor center (intratumoral budding; ITB) of primary tumors. Previous studies have shown that tumor buds are also present in colorectal liver metastases (CRLM). Data on the prognostic and predictive role in this clinical context are still sparse and no standardized approach to evaluate budding in CRLM has been published so far. This study aimed to analyze and correlate perimetastatic (PMB) and intrametastatic budding (IMB) on H&E and pancytokeratin staining, compare it to budding results in corresponding primary tumors and to propose a standardized scoring system in CRLM as the basis for future studies. Tumor tissue of 81 primary tumors and 139 corresponding CRLM was used for ngTMA construction. For each primary tumor and metastasis, two punches from the center and two punches from the periphery from areas with highest tumor budding density were included. TMA slides were stained for H&E and pancytokeratin (Pan-CK). PTB, ITB, PMB and IMB were analyzed and classified as bd1, bd2 and bd3 according to ITBCC guidelines. ITB and PTB as well as IMB and PMB showed significant correlation on H&E and Pan-CK staining. No correlation was found for tumor bud counts in primary tumors and corresponding metastases. The agreement for categorized tumor bud counts showed fair to good agreement for metastases and poor agreement for primary tumors between different classes on H&E and Pan-CK staining. Based on our results, tumor budding in primary tumors and CRLM seems to be different processes which might be the results of differing surrounding microenvironments. The evaluation of tumor budding in CRLM is challenging in cases without desmoplastic stroma reaction or intense perimetastatic ductular reaction. We therefore propose to evaluate tumor budding only in metastases with desmoplastic stroma reaction based on H&E staining since important morphological features are obscured on Pan-CK staining.